Echo-assisted impulsive alignment of room-temperature acetone molecules - Junyang Ma; L. H. Coudert; F. Billard; M. Bournazel; B. Lavorel; Jian Wu; G. Maroulis; J.-M. Hartmann; O. Faucher (Physical Review Research, 2021)
We experimentally and theoretically investigate the field-free alignment of the asymmetric-top acetone molecule. Our study shows that the production of postpulse aligned molecules in dense samples (0.05–0.2 bar) of room-temperature acetone using a single-pulse excitation can be significantly improved by rotational alignment echoes induced in a two-pulse excitation scheme. We report the observation of fractional echoes that can be used to reveal the nonlinearity of the molecular system. In a proof-of-principle experiment, a prealigned sample of acetone is also used for third-harmonic generation. The analysis of the experimental data with numerical simulations based on quantum and classical models enables the determination of the collisional decay rate of acetone alignment, as well as a test of the static, second-order, electric hyperpolarizabilities of the molecule derived from ab initio calculations presented in this work.